Enhanced Lithium Extraction from Brines: Prelithiation Effect of FePO4 with Size and Morphology Control - Xiaoyu Zhao; Shuo Yang; Xiuli Song; Yushuang Wang; Hui Zhang; Muhan Li; Yanfei Wang (Advanced Science)
Abstract Extracting lithium resources from seawater and brine can promote the development of the new energy materials industry. The electrochemical method is green and efficient. Iron phosphate (FePO4) crystal, with its 1D ion channel, holds significant potential as a primary lithium extraction electrode material. Li+ encounters a substantial concentration disadvantage in brines, and the co‐intercalation of Na+ diminishes Li+ selectivity. To address this issue, this work enhances the energy barrier for Na+ insertion through prelithiation strategies applied to the 1D channels of FePO4 crystal, thereby improving Li+ selectivity, and further investigating the prelithiation effect with particle size and morphology control. The results indicate that the Li(4C‐40%)FePO4// Activated carbon(AC) system enhances selectivity of lithium. The Li(4C‐40%)FePO4 with size diameter of 2500 nm demonstrates an energy consumption of 0.79 Wh mol−1 and a purity of 97.94% for lithium extraction at a unit lithium extraction of 5.93 mmol g−1 in simulated brine. Li(4C‐40%)FePO4‐nanoplates demonstrate the most optimal lithium extraction performance among the three morphologies due to their lamellar structure's short ion diffusion path in the [010] channel, favoring Li+ diffusion. The diffusion energy barriers of Li+ and Na+ are calculated using Density Functional Theory (DFT) before and after prelithiation, showing good agreement with experimental results.